Mecca in Morocco - Al-Ajarma, Kholoud (Edinburgh University Press, 2025)
This book concerns the ways in which the Muslim pilgrimage to Mecca, the Hajj, is embedded in Moroccan society. Approaching pilgrimage from the perspective of lived religion, the book seeks to answer the question: How does Hajj feature in the everyday lives of Moroccans and how are Moroccan views on Hajj are negotiated in pilgrims’ micro-practices? The red thread that runs through this book is the argument that although the Hajj is performed in a place far away from Morocco, taking Moroccans out of their daily life worlds, the practices, experiences, and the meanings that they attach to Hajj are shaped by, and in turn go on to shape, their life and world upon return. The chapters of the book demonstrate - - from different perspectives - how the everyday Moroccan context shapes pilgrims’ perceptions of their experience in Mecca and, in return, how after having completed Hajj they position themselves and are positioned as members of their community. Particularly important are the myriad ways in which the experience of being a ḥājj/ ḥājja shapes their everyday life.